The Analgesic and Emotional Response to Intravenous Lidocaine Infusion in the Treatment of Postherpetic Neuralgia: A Randomized, Double-Blinded, Placebo-controlled Study. Issue 11 (November 2018) - Liu, Hui; Lu, Fan; Zhou, Dan; Yin, Yan; Li, Jun; Yang, BangXiang; Song, Li; Ye, Ling; Xiao, Hong
Abstract : Objectives: This study evaluated the analgesic efficacy and emotional response to intravenous lidocaine infusion compared with placebo in patients with postherpetic neuralgia (PHN). Methods: In this randomized, double-blinded study, patients with PHN received 5 mg/kg intravenous lidocaine infusion or placebo. The primary outcome was pain measured by Visual Analogue Scale, Von Frey, and area of allodynia. Moreover, emotional status of anxiety and depression were evaluated by Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS). Quality of life was assessed by Short Form Health Survey 36. Results: In total, 197 patients were enrolled and eligible data were collected from 183 of those patients. The Visual Analogue Scale scores were reduced to a minimum at 2 weeks (2.74, 2.99) after infusion, but no significant difference was found between the lidocaine and placebo groups. Similar changes were also found in mechanical pain threshold and area of allodynia. However, the lidocaine group was associated with a statistically significant reduction in consumption of analgesics with a relative risk of 6.2 (95% confidence interval [CI], 2.24-17.16). Lidocaine infusion also significantly improved the anxiety and depression status; the values of mean change in anxiety and depression were 3.89 (95% CI, 1.43-6.35) and 4.3 (95% CI, 0.63-7.98), respectively, at 2 weeks. Moreover, improvement was exhibited in Short Form Health Survey 36 health status, with the mean change of 49.81 (95% CI, 28.17-71.46) at 1 week, in particular scores on vitality, physical and emotional role functioning, and mental health. Conclusions: The analgesic response of 5 mg/kg lidocaine intravenous infusion is comparable to placebo in patients with PHN, but intravenous lidocaine infusion significantly reduced total analgesic consumption, and improved the overall emotional and health status.